Características fisiológicas e nutricionais do capim Tifton 85 (Cynodon spp.) e Capim vaquero (Cynodon dactylon) em função da idade de rebrota - Ströher, Sandra Mara (2015)
This study aimed to evaluate the gas exchange, enzyme activity, dry matter production and nutritional value over the grass growth Vaquero and Tifton 85 grass depending on the age of regrowth, between the months of August to October 2014 hay production area. The experimental design was a randomized block with split plot with two treatments and five replications. The treatments correspond to forage (Tifton 85 and Vaquero) and the times were the days of regrowth (15, 22, 29, 36 and 43 days). The analyzed nutritional variables were dry matter production, in vitro dry matter digestibility (IVDMD), crude protein (CP), dry matter (DM), neutral detergent fiber (NDF), acid detergent fiber (ADF), insoluble protein neutral detergent (IPND), insoluble protein, acid detergent (IPAD), lignin, cellulose, hemicellulose and mineral matter (MM). The analysis of gas exchange were made from the net assimilation rate of CO2, stomatal conductance, internal CO2 concentration, leaf transpiration, relative humidity, leaf temperature, efficiency in water use, intrinsic efficiency in water use and efficiency intrinsic carboxylation. For the structural characteristics were collected plant height data, stem diameter, number of green leaves and the number of dead leaves. The biochemical assessments are based on variables such as total protein, insoluble carbohydrate, peroxidase activity (POX) activity and catalase (CAT), and analyzes for the SPAD index and electrical conductivity. It was found that the dry matter production was similar (P> 0.05) between the two fodder. PB Vaquero grass has performed better (P <0.05) at 15 and 29 days of regrowth. The ADF contents were higher in Tifton 85 grass at 15 and 36 days of regrowth. IVDMD concerning the grass Tifton 85 was higher than 29, 36 and 43 days of age, while the Vaquero grass showed better levels at 15 and 22 days of regrowth. The net CO2 assimilation was similar between the forage, except at 22 days of age in the grass Vaquero was superior, where it expressed greater stomatal conductance at 29 days of age when compared to the Tifton 85 grass and greater concentration CO 2 for 22 and 29 days of regrowth. As for the efficient use of water and intrinsic efficiency of water use, the Tifton 85 grass showed the best values at 22 and 29 days of regrowth, similar to Vaquero in other times, however, the Tifton 85 grass was superior to 22 and 29 days of growth when assessing the intrinsic efficiency of carboxylation. Tifton 85 grass had higher plant height to 15, 22 and 36 days of regrowth, with average values of 16.3; 18.8 and 25.1 cm, respectively. For the SPAD index, the grass Tifton 85 was superior for all time periods, showing also lower electrical conductivity. On days 15, 29 and 36 days of regrowth, the grass Tifton 85 had higher carbohydrate values soluble to those found for the Vaquero. The evaluated grasses expressed similar production of dry matter, but were influenced by low night temperature recorded during the experiment. As for nutritional value, the grass Vaquero has better nutritional value until 29 days of age and the Tifton 85 grass, despite the high NDF, demonstrates proper digestibility during the 43 days of regrowth. Vaquero grass externalizes greater stomatal conductance and internal CO2 concentration at 22 and 29 days, however, the Tifton 85 grass shows a more efficient use of water and intrinsic efficiency of water use at 22 and 29 days of regrowth, and thus more efficient, i.e., less loss of water in CO2 fixation. The recommended height for cutting and grass Tifton 85 and Vaquero grass were between 30 and 25 cm, respectively. The grass Tifton 85 has a higher SPAD index and thus shows have better photosynthetic characteristics due to higher concentration of chlorophyll, in addition to lower electrical conductivity. The grass Tifton 85 exposed higher catalase activity (CAT) and appeared to suffer greater stress at nights with low temperatures. The contents peroxidase (POX) increased with peak activity lignification and catalase (CAT) after 29 days of regrowth to Tifton 85. The grass Vaquero expressed higher resistance to cold stress, but on the other hand, suffered stress with increased catalase activity (CAT) caused by leafhopper-of-grazing herbivory